2020
DOI: 10.1371/journal.pone.0239279
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities of caregivers and individuals with dementia with Lewy bodies: An interview study

Abstract: Background Funding bodies are placing increased emphasis on patient and public involvement in research, but the research priorities of individuals and caregivers living with dementia with Lewy bodies (DLB) are unknown. Method Investigators conducted telephone interviews with individuals living with DLB and caregivers. Participants were recruited from a Lewy Body Dementia Association Research Center of Excellence. Interviews employed a semi-structured questionnaire querying research needs in different categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Other studies have examined the role of dyadic communication and quality of intimate relationships between caregivers and care recipients [49]. Findings such as these provide further support that psychosocial constructs may be more dependent on care recipient caregiver dyad characteristics and the current symptoms than the underlying cause of those symptoms, and align with caregiver interests in expanding research topics in DLB, PDD, and AD [50].…”
Section: Discussionsupporting
confidence: 53%
“…Other studies have examined the role of dyadic communication and quality of intimate relationships between caregivers and care recipients [49]. Findings such as these provide further support that psychosocial constructs may be more dependent on care recipient caregiver dyad characteristics and the current symptoms than the underlying cause of those symptoms, and align with caregiver interests in expanding research topics in DLB, PDD, and AD [50].…”
Section: Discussionsupporting
confidence: 53%
“…While some needs and concerns could be aligned with more than one category, there were no new categories that emerged outside of the five domains from the needs and concerns framework. Although the sample was small, needs and concerns reflected those described in the literature (Armstrong et al, 2019, 2020b; Galvin et al, 2010a; Killen et al, 2016; Leggett et al, 2011). Mirroring similar studies, participants described the need for more information about the disease, prognosis, and what to expect when caring for someone with LBD (Armstrong et al, 2019, 2020b; Galvin et al, 2010b; Killen et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…However, with these studies the diagnoses were self-reported, respondents self-selected, and responses were limited by an online survey format. Qualitative LBD caregiver studies identified in the literature focused primarily on information needs at end-of-life and caregiver research priorities (Armstrong et al, 2019(Armstrong et al, , 2020a(Armstrong et al, , 2020b. While these studies yielded important information and established a baseline understanding of caregiver needs, a qualitative study of the needs and concerns of caregivers of persons with LBD is needed to advance the science in this area.…”
mentioning
confidence: 99%
“…There is no consensus on the high-priority symptoms for evaluation, as individuals with LBD may have variable degrees of cognitive, neuropsychiatric, autonomic, motor, or sleep disturbances [6,71].…”
Section: Picking the Appropriate Clinical Outcome(s) For Lbd Trialsmentioning
confidence: 99%